Т. 2; Сборник аннотированных фольклорных и бытовых текстов обско-енисейского языкового ареала - Фильченко А. Ю. Андрей Юрьевич; Потанина О. С. Ольга Сергеевна; Крюкова Е. А. Елена Александровна; Байдак А. В. Александра Владимировна; Максимова Н. П. Наталья Петровна; Лемская В. М. Валерия Михайловна; Ким А. А. Антонина Александровна; Гусев В. Ю. (Изд-во Аграф-Пресс, 2012)
Заглавие с экрана